Euro- US Real Exchange Rate Dynamics: How Far Can We Push Equilibrium Models? - Aydan Dogan (University of Kent, School of Economics, 2014)
This paper re-assesses the problem of general equilibrium models in matching the behaviour of real exchange rate. We do so by developing a two country general equilibrium model with non-traded goods, home bias, incomplete markets and partial degrees of pass through as well as nominal rigidities both in the goods and labour markets. We combine this comprehensive framework with a data consistent shock structure. Our key finding is that presenting an encompassing model structure improves the performance of the model in addressing the behaviour of the real exchange rate but this improvement is at the expense of failing to replicate some other characteristics of the data, such as high consumption volatility and negative cross-country consumption correlation. We argue that the ability of a general equilibrium model to account for the features of the data is closely related to the predominant driving source of the fluctuations.
Keywords: F31; F32; F41; 330; Real Exchange Rates; Non-traded goods; Incomplete Asset Markets; Imperfect Exchange Rate Pass Through; Nominal Rigidities